Life-cycle of Angosto Chico Inciso vessels. Different methods in the analysis of a particular style from Quebrada de Humahuaca (Argentina) - Scaro, Agustina (2020)
Ceramics are part of the material dimension of practice, inserted into a process by which human objects and agents are reciprocally constituted. In this way, both daily activities and everyday objects are socially significant. Therefore, it is necessary to focus on a broader aspect of social life that goes beyond “the symbolic”. In this sense, a comprehensive ceramic analysis that integrates stylistic, technological and functional aspects is relevant to understand social, symbolic and ideological dimensions in everyday activities of the groups that developed and consumed ceramic vessels. Within this framework, the interrelated analysis of functional, technological, morphological and iconographic aspects allows understanding how a particular way of doing was configured and use. Angosto Chico Inciso was considered one of the local late pre-Hispanic ceramic styles of Quebrada de Humahuaca (North of Argentina), although its foreign origins and the great variety within the style was soon evidenced. Recent petrographic studies have shown that these vessels present both a local and foreign manufacture. In this paper we present the analysis of Angosto Chico Inciso ceramics recovered in a sector of Quebrada de Humahuaca, considering diverse approaches to determine the stylistic variety within this group of vessels, their technological traits and the function they could have had in different pre-Hispanic moments. Stylistic studies that consider iconographic and morphological aspects, technological and use-wear analysis were carried out in 38 fragmented vessels from Esquina de Huajra, Pucara de Volcán, and El Pobladito sites, covering pre-Inca and Inca occupations. Studies determined the production and use of Angosto Chico Inciso vessels as early as the 13th century, both in domestic and public contexts. These vessels correspond to local and non-local manufacturing. Stylistic and technological studies have revealed the presence of two modalities of Angosto Chico Inciso that correspond to the two different manufactures.